A method for producing asphalt containing rubber from used tires

By processing ELT rubber as an inert material and integrating it into asphalt through heat treatment and mixing, the method overcomes the limitations of existing technologies, allowing substantial rubber use and enhancing asphalt performance and sustainability.

JP7602036B2Active Publication Date: 2024-12-17BRIDGESTONE EURO NV SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023527123
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-06
Filing Date
2021-11-05
Publication Date
2024-12-17
Estimated Expiration
2041-11-05

AI Technical Summary

Technical Problem

Existing methods for incorporating rubber from end-of-life tires (ELT) into asphalt are limited by the small amount of rubber that can be used, posing barriers to significant recycling and performance benefits.

Method used

Processing ELT rubber to act as an inert material and partial replacement for stone aggregate, involving heat treatment, mixing with stone aggregate and bitumen, and surface polishing to enhance dispersion and compaction.

Benefits of technology

Enables the use of significant amounts of ELT rubber in asphalt, improving performance and environmental sustainability without high-temperature melting operations, ensuring worker safety and effective pavement reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602036000001
    Figure 0007602036000001
  • Figure 0007602036000002
    Figure 0007602036000002
  • Figure 0007602036000003
    Figure 0007602036000003
Patent Text Reader

Abstract

The manufacturing method of asphalt is to make the density of asphalt 1.0-1.5g / cm 3 and a mixing step of mixing the rubber granules from the heat treatment step with stone aggregate and bitumen to obtain asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for using rubber obtained from used tires in the preparation of asphalt. [Background technology]

[0002] In this specification and below, the term asphalt refers to a bituminous conglomerate used in the construction of road pavements.

[0003] Generally, road asphalt is composed of about 94% stone aggregates and about 6% bitumen.

[0004] The use of rubber from post-wear tyres (PFU) or end-of-life tyres has been known for some time (from now on the English expression "ELT: end-of-life tyre", an acronym for end-of-life tyre, will be used). In addition to the environmental benefits of using waste material, the use of ELT rubber also offers advantages in terms of reducing the rolling noise generated by the dynamic contact of the tyre with the pavement.

[0005] The solutions implemented so far suggest two ways of using rubber powder in ELT. The first method, generally known as the "dry" technique, implies the direct addition of the powder to the aggregates and bitumen during the mixing step of the bituminous aggregate, the amount of powder added ranges from 1 to 2% by weight relative to the mixture. The other method, generally known as the "wet" technique, implies mixing the bitumen with the powder and reacting it at a temperature such that the rubber particles swell, thereby obtaining what is indicated by the English phrase "Crumb Rubber Modified Binder (CRMB)". The amount of powder introduced in the CRMB varies between about 15 and 22% relative to the weight of the bitumen. Summary of the Invention

[0006] Considering that according to these known techniques the powders used in the "dry" and "wet" techniques only amount to about 2% of the weight of the asphalt, it is clear that the solutions implemented so far allow a very low amount of ELT-rubber to be used in the asphalt. Such a limitation, in addition to being an obstacle to significant recycling of ELT-rubber in asphalt, precludes the possibility of investigating what possible performance advantages of the asphalt could result from the presence of more ELT-rubber.

[0007] Therefore, a need was felt to be able to use larger amounts of ELT rubber in asphalt than was possible with the known prior art discussed above.

[0008] The inventors of the present invention have developed a solution that can satisfy the aforementioned need by processing ELT rubber in such a way that it can be used as an inert material and as a partial substitute for stone aggregate, i.e., by overcoming the need to dissolve stone aggregate in the asphalt for CRMB production. [Means for solving the problem]

[0009] The object of the present invention is to provide a method for producing asphalt having a density of 1.0 to 1.5 g / cm 3 , preferably 1.2 to 1.3 g / cm 3 a heat treatment step, in which rubber granules obtained from a used tyre granulation process are subjected to a temperature of 80-300°C, preferably 100-200°C, for a period of time required to obtain rubber granules of 1000 g / m2, and a mixing step, in which the rubber granules from the heat treatment step are mixed with stone aggregate and bitumen to obtain asphalt.

[0010] Preferably, the mixing step includes a first mixing operation in which the stone aggregate and bitumen are mixed at a temperature of 150-200°C, and a second mixing operation in which rubber granules are added to the mixture from the first mixing operation.

[0011] Such a mixing sequence improves the dispersion of the granules within the resulting asphalt.

[0012] Preferably, the rubber granules from the heat treatment step comprise between 1 and 30 volume percent of the amount of inert material contained within the asphalt.

[0013] In this specification and below, the term inert material refers to the combination of stone aggregate and ELT rubber granules.

[0014] Preferably, the rubber granules resulting from the granulation process have a substantially polyhedral conformation with a ratio of maximum to minimum size of less than 2.

[0015] Indeed, it has been found that granules with similar three-dimensional dimensions give better results.

[0016] Preferably, the rubber granules resulting from the granulation process are sized to pass through a sieve having a mesh size of between 10 mm and 1.5 mm, more preferably having a mesh size of between 2.0 mm and 6.0 mm.

[0017] Preferably, the method comprises a pre-heating step prior to said heat treatment step, in which the rubber granules obtained from the ELT granulation process are subjected to a temperature of from 120 to 200° C. for a period of from 15 to 30 hours.

[0018] Preferably, the method comprises a surface treatment step after said heat treatment step, in which the rubber granules from the heat treatment are subjected to a surface grinding operation.

[0019] The grinding operation results in a powder that provides additional compaction of the asphalt, and furthermore, the inventors believe it is crucial that this powder comes from the outer layer of the pretreated rubber granules.

[0020] Preferably, the method comprises a final heat treatment step after said surface treatment step and before said mixing step, during which the rubber granules obtained from the surface treatment process have a density of 1.0 to 1.5 g / cm 3 , preferably 1.2 to 1.3 g / cm 3 The rubber granules are subjected to a temperature of 80 to 300° C., preferably 100 to 200° C., for a period of time required to obtain the rubber granules.

[0021] A further object of the present invention is to provide a granulated granule having a size such that it passes through a sieve with a mesh size of up to 10 mm and a density between 1.0 and 1.5 g / cm obtained from a used tire granulation process. 3 , preferably 1.2 to 1.3 g / cm 3 The present invention relates to rubber granules and / or rubber powder that are exposed to a temperature of 80 to 300° C. for a period of time required to obtain rubber granules and / or rubber powder of the present invention.

[0022] Preferably, the granules and / or powder are subjected to a pre-heating step prior to the heat treatment step, in which the rubber granules and / or rubber powder obtained from the ELT granulation process are exposed to a temperature of 120-200°C for a period of 15-30 hours.

[0023] Preferably, said granules and / or powder are subjected to a surface treatment step after said heat treatment step, wherein the rubber granules and / or rubber powder from the heat treatment are subjected to a surface grinding operation.

[0024] Preferably, the granules and / or powder are subjected to a final heat treatment step after the surface treatment step, during which the rubber granules and / or rubber powder obtained from the surface treatment process have a density of 1.0 to 1.5 g / cm 3 , preferably 1.2 to 1.3 g / cm 3 The rubber granules and / or rubber powder are exposed to a temperature of 80 to 300° C., preferably 100 to 200° C., for a period of time required to obtain the rubber granules and / or rubber powder.

[0025] The maximum diameter of the rubber powder is 1.5 mm.

[0026] The following are non-limiting embodiments given by way of example only. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Two bituminous aggregate mixtures according to the invention were prepared.

[0028] The two aggregates differ from each other according to the type of treatment that is applied to the rubber granules obtained from the ELT: in particular, the first bituminous aggregate mixture is obtained using rubber granules that have been subjected to only a thermal treatment, whereas the second bituminous aggregate mixture is obtained using rubber granules that have been subjected to both a thermal treatment and a mechanical surface treatment.

[0029] In the following examples, the maximum diameter of the basalt material is 8mm, the maximum diameter of the fine gravel material is 6mm, and the maximum diameter of the basalt sand material is 4mm, and the filler material and reinforcing fibers must meet the requirements shown in the following tables.

[0030] [Table 1]

[0031] [Table 2]

[0032] Granules with dimensions of 2.5-4.0 mm were taken from rubber obtained from the ELT granulation process.

[0033] These granules are prepared according to the following sequence: ○ 175℃ for 24 hours The materials were heated at 250°C for 10 hours with periodic mixing every hour. The heat treatment step was carried out in a laboratory static oven at atmospheric pressure.

[0034] The density of the granules obtained from the above heat treatment is >1.25g / cm 3 It is.

[0035] During treatment at 250°C, both density and water absorption were checked periodically.

[0036] The rubber granules produced as described above were used in the preparation of a bituminous aggregate mixture.

[0037] Table 1 shows the composition of the inert material of the first bituminous aggregate mixture in both volume percent and weight percent. [Table 3]

[0038] As explained below, the bituminous aggregate mixture also contains bitumen in an amount equal to 8% by weight relative to 100% by weight of the inert material.

[0039] The procedure for preparing the bituminous aggregate mixture is described below.

[0040] The basalt, basalt sand, and bitumen were each heated separately from the other ingredients until they reached 165°C. Once the temperature reached 165°C, the aforementioned ingredients were added to the mixer, which was then operated at a speed of about 80 rpm. After mixing for about 1 minute, the reinforcing fibers were added. After mixing for about 1 minute, the fillers were added. After mixing for about 1 minute, the pretreated ELT granules were added. After about 1 minute, the preparation was completed.

[0041] A portion of the mixture was immediately used to measure the maximum density (according to UNI EN 12697‐5).

[0042] In preparing the test specimens, the mixed material at a temperature of 165° C. was subjected to a thickening process by rotary press (50 rpm rotary press).

[0043] After thickening was complete, the test specimen was removed from the die and allowed to cool to room temperature.

[0044] After 24 hours, the test specimens were cut as per specifications to be subjected to subsequent mechanical tests (ITS, ITSR, CTI).

[0045] The parameters studied were: ITS parameters for assessing mechanical resistance (UNI EN 12697-23), ITSR parameters for assessing sensitivity to water (UNI EN 12697-12), CTI parameters for assessing deformability indices (UNI EN 12697-23) It was.

[0046] Table II shows the results obtained for the values ​​of the aforementioned parameters. [Table 4]

[0047] Table III shows the volumetric property values ​​as a function of the rotary press speed.

[0048] In particular, the volumetric properties investigated were the percentage of voids (%Vv), percentage of bitumen volume (%Vb), percentage of aggregate volume (%Vag), percentage of voids in the dry mix (%VMA), percentage of voids filled with bitumen (%VFA), actual density of the samples (Gmb), maximum density (Gmm), and degree of thickening (%Gmm).

[0049] [Table 5]

[0050] Granules with dimensions of 2.5-4.0 mm were taken from rubber obtained from the ELT granulation process.

[0051] These granules were subjected to a first heat treatment step in a static oven at atmospheric pressure at a temperature of 150° C. for 48 hours.

[0052] The granules from the first heat treatment step were subsequently subjected to a surface treatment step in order to increase the specific surface area of ​​the granules themselves. During the surface treatment step, the granules were passed five times through two passes of horizontal axis rollers (P40 sandpaper) of a "Molino" machine.

[0053] The granules from the surface treatment step are subsequently subjected to a final heat treatment step in a static oven at atmospheric pressure until the granule density reaches 1.26 g / cm 3 The granules were exposed to a temperature of 150° C. for 120 hours until a temperature of

[0054] During the final heat treatment step, both density and water absorption were checked periodically.

[0055] The rubber granules produced as described above were used in the preparation of a bituminous aggregate mixture.

[0056] Table IV shows the composition of the inert material of the second bituminous aggregate mixture in both volume percent and weight percent. [Table 6]

[0057] As explained below, the bituminous aggregate mixture also contains bitumen in an amount equal to 5.5% by weight based on 100% by weight of the inert material.

[0058] The procedure for preparing the bituminous aggregate mixture is described below.

[0059] The basalt, fine gravel, basalt sand, and bitumen were each heated separately from the other ingredients until they reached 165°C. Once the temperature reached 165°C, the aforementioned ingredients were added to the mixer, which was then operated at a speed of about 80 rpm. After mixing for about 1 minute, the reinforcing fibers were added. After mixing for about 1 minute, the fillers were added. After mixing for about 1 minute, the pretreated ELT granules were added. After about 1 minute, the preparation was completed.

[0060] The mixtures prepared as described above were processed in order to characterize them in terms of both density and mechanical parameters.

[0061] The mixture processing procedures, as well as the parameters and characterization procedures, are the same as those described above for the first bituminous aggregate mixture.

[0062] Table V shows the results obtained for the values ​​of the parameters mentioned above. [Table 7]

[0063] Table VI gives the values ​​of the above mentioned volumetric properties as a function of the rotary press speed. [Table 8]

[0064] From the data presented in Tables II, III, V and VI, anyone skilled in the art can recognize that the asphalt obtained from the process that is the object of the present invention meets all the necessary requirements for effective use.

[0065] The method that is the object of the present invention offers the great advantage of allowing the use of significant amounts of ELT-rubber granules, which are improved in such a way that they can be handled in the same way as stone.

[0066] This method, which is the object of the present invention, also offers the advantage of avoiding high-temperature melting operations of the granules obtained from the ELT in the bitumen, which offers clear advantages in terms of worker safety.

[0067] The results of the water sensitivity tests carried out on the aggregate mixtures obtained according to the invention demonstrate significant advantages with regard to the possibility of introducing a high proportion of granules obtained from ELT into bituminous aggregates, without the need to use a high proportion of bitumen. Considering that the state of the art for rubber powder mixtures to date prescribes the use of a bitumen content of 8% or more for a proportion of granules obtained from ELT of only 2% by weight, the resulting improvement in the environmental sustainability of the pavement implying the reuse of granules obtained from ELT is evident.

Claims

1. A method for producing asphalt, comprising the steps of: 3 1. A method for the manufacture of asphalt comprising a heat treatment step, exposing rubber granules obtained from an end of life tyre (ELT) granulation process to a temperature between 80 and 300° C. for a period of time required to obtain rubber granules of 100% by weight, and a mixing step, mixing the rubber granules from the heat treatment step with stone aggregate and bitumen to obtain asphalt, comprising a surface treatment step after the heat treatment step, in which the rubber granules from the heat treatment are subjected to a surface grinding operation.

2. 10. The method of claim 1, wherein during the heat treatment step, the density is between 1.2 and 1.3 g / cm 3 1. A process according to claim 1, characterized in that said rubber granules obtained from a used tyre granulation process are subjected to a temperature of 100-200° C. for a period of time required to obtain a rubber granule of

3. 3. The method according to claim 1 or 2, characterized in that the mixing step includes a first mixing operation in which the stone aggregate and the bitumen are mixed at a temperature of 150-200°C, and a second mixing operation in which the rubber granules are added to the mixture from the first mixing operation.

4. The method of any one of claims 1 to 3, wherein the rubber granules from the heat treatment step constitute 1 to 30 volume percent of the amount of inert material contained within the asphalt.

5. The method according to any one of claims 1 to 4, wherein the rubber granules obtained from the granulation process have a substantially polyhedral structure and are characterized in that the ratio between the largest and smallest size is less than 2.

6. The method according to any one of the preceding claims, characterized in that the rubber granules obtained from the granulation process are of a size such that they pass through a sieve having a mesh size between 10 mm and 1.5 mm.

7. The method according to any one of the preceding claims, characterized in that the rubber granules obtained from the granulation process are sized to pass through a sieve having a mesh size of between 2.0 mm and 6.0 mm.

8. 2. The method according to claim 1, further comprising a final heat treatment step after the surface treatment step and before the mixing step, during which the rubber granules obtained from the surface treatment process are mixed with a rubber granule having a density of 1.0 to 1.5 g / cm 3 3. A process according to claim 2, characterized in that the rubber granules are subjected to a temperature of from 80 to 300° C. for a period of time required to obtain a rubber granule of

9. 9. The method according to claim 8, wherein during the final heat treatment step, the rubber granules obtained from the surface treatment process are treated with a granule blend having a density of 1.2 to 1.3 g / cm 3 3. A process according to claim 2, characterized in that the rubber granules are subjected to a temperature of from 100 to 200° C. for a period of time required to obtain a rubber granule of

Citation Information

Patent Citations

  • Asphalt composition, method for producing the same and pavement using the same

    JP2002080723A

  • Reclaimed rubber, and elastic molded article using it

    JP2002201204A

  • Method for producing asphalt mixture and asphalt mixture

    JP2009209197A